Resveratrol inhibits Src tyrosine kinase, STAT3, and Wnt signaling pathway in collagen induced arthritis model. (29th November 2018) - Oz, Burak; Yildirim, Ahmet; Yolbas, Servet; Celik, Zulfinaz Betul; Etem, Ebru Onalan; Deniz, Gulnihal; Akin, Mustafa; Akar, Zeynel Abidin; Karatas, Ahmet; Koca, Suleyman Serdar
Abstract: Resveratrol, a phytochemical, acts several cellular signaling pathways and has anti‐inflammatory potentials. The purpose of this study is to research the therapeutic effect of resveratrol in collagen‐induced arthritis (CIA) model in rats and whether resveratrol affects the activities of signaling pathways those are potent pathogenic actors of rheumatoid arthritis. Arthritis was induced by intradermal injection of chicken type II collagen combined with incomplete Freund's adjuvant in Wistar albino rats. One day after the onset of arthritis (day 14), resveratrol (20 mg/kg/day) was given via oral gavage, until day 29. The paws of the rats were obtained for further analysis. Tissue Wnt5a, mitogen‐activated protein kinase (MAPK), Src tyrosine kinase and signal transducer, and activator of transcription‐3 (STAT3) mRNA expressions were determined by real‐time polymerase chain reaction. Resveratrol ameliorated the clinical and histopathological (perisynovial inflammation and cartilage‐bone destruction) findings of inflammatory arthritis. The tissue mRNA expressions of Wnt5a, MAPK3, Src kinase, and STAT3 were increased in the sham group compared to the control group. Resveratrol supplement decreased their expressions. The present study shows that Src kinase, STAT3, and Wnt signaling pathway are active in the CIA model. Resveratrol inhibits these signaling pathways and ameliorates inflammatory arthritis. © 2018 BioFactors, 45(1):69–74, 2019